2005
DOI: 10.1002/maco.200503864
|View full text |Cite
|
Sign up to set email alerts
|

The study of the La(NO;3)3 inhibition on X70 pipeline steel in 3.0(wt.%) NaCl solution

Abstract: Lanthanum nitrate has been investigated as corrosion inhibitor of X70 pipeline steel in 3.0 (wt.%) NaCl solution using electrochemical techniques such as potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) in conjunction with scanning electron microscopy (SEM) and energy dispersive X-ray detector (EDX) techniques. The results showed that La(NO 3 ) 3 belonged to the film-formed mixed inhibitors, which can form a compact network over the whole surface of X70 pipeline steel. The inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Unlike the multiple corrosion studies in CO 2 -free electrolytes where it has been reported that the protection mechanism of rare earth is due to their precipitation (as oxides and hydroxides) by hydrolysis reactions of their metallic cations with the OH − ions produced in the cathodic sites [19,[23][24][25][37][38][39][40], a different mechanism was observed in this study, namely, CO 2 capture and precipitation of lanthanum carbonate (La 2 (CO 3 ) 3 ) as a protective barrier.…”
Section: Co 2 -Capture and Protection Mechanismmentioning
confidence: 60%
“…Unlike the multiple corrosion studies in CO 2 -free electrolytes where it has been reported that the protection mechanism of rare earth is due to their precipitation (as oxides and hydroxides) by hydrolysis reactions of their metallic cations with the OH − ions produced in the cathodic sites [19,[23][24][25][37][38][39][40], a different mechanism was observed in this study, namely, CO 2 capture and precipitation of lanthanum carbonate (La 2 (CO 3 ) 3 ) as a protective barrier.…”
Section: Co 2 -Capture and Protection Mechanismmentioning
confidence: 60%
“…Each of them is associated with the slope changes of the relation log f vs log |Z|, in the three regions of the frequency. e formation and evolution of the rst two time constants can be related to the typical mechanism of precipitation of hydroxides and oxides for corrosion process inhibited by the addition of compounds based on rare earths [21,[33][34][35][36]. In general, the formation of the protective lms is due to the hydrolysis reactions of the lanthanide cations with the OH − ions generated at the cathodic sites.…”
Section: Electrochemical Impedance Spectroscopy Measurementsmentioning
confidence: 99%
“…e increase in pH of the cathodic sites causes the precipitation of compounds of the type Me(OH) 3 , which subsequently are transformed to more stable metal oxides (Me 2 O 3 ). e mechanism of precipitation of both rare earth oxides and hydroxides has been cited in the literature previously [7,[27][28][29][30]. In general, the hydrolysis reaction of lanthanide cations (Ln) can occur according to the following reactions:…”
Section: Electrochemical Impedance Spectroscopy Measurementsmentioning
confidence: 99%